The basal tectonic mélange of the Cabo Ortegal Complex (NW Iberian Massif): a key unit in the suture of Pangea - Arenas, R.; Sánchez Martínez, S.; Castiñeiras, P.; Jeffries, T.E.; Díez Fernández, R.; Andonaegui, P. (Journal of Iberian Geology, 2009)
Recent field work and mapping in the lower units of the Cabo Ortegal Complex provided new data about the tectonic mélange that appears in the lowest structural position: the Somozas Mélange. This mélange unit with average thickness of 1800 m is restricted to the eastern part of the complex, and is located at the advancing front of the allochthonous complexes of NW Iberia. Three rock units are involved in the mélange: 1) an ophiolitic mélange consisting of igneous rocks mixed with serpentinites; 2) a metasedimentary unit with phyllites and phyllonites, with scarce conglomerates, marbles and quartzites; 3) high-T metamorphic rocks with varied types of amphibolites and orthogneisses. Two granitic rocks within the ophiolitic mélange were dated using U-Pb zircon geochronology at 527 ± 2 Ma and 499 ± 1 Ma. Two different series of igneous rocks can be distinguished in this mélange. The first series consists of gabbros, diorites, granitoids and basalts-basaltic andesites with calc-alkaline affinities. The second series contains common basaltic rocks, diabasic dikes and gabbros with chemical compositions typical of island-arc tholeiites. Both igneous series shared a common geographic setting, but the island-arc tholeiites are younger than the calc-alkaline igneous rocks. The two igneous series were probably generated in a mature volcanic arc located along the periphery of Gondwana. In the metasedimentary unit, a conglomerate from a large tectonic block included in serpentinites yielded age populations of detrital zircons suggesting that the sediments were deposited along the periphery of the West-African Craton. This conglomerate contains a large number of zircons (n = 24) with ages ranging 630-464 Ma, probably representing the chronology of the Pan-African event, including the magmatic activity in the volcanic arc where the igneous lithologies involved in the mélange were generated. The maximum age of sedimentation for this conglomerate is estimated as latest Cambrian – earliest Ordovician, and constraints the end of the magmatic activity in the volcanic-arc. Within the unit of high-T rocks, an orthogneiss yields a U-Pb protolith age of 485 ± 6 Ma, which is similar to other ages of igneous rocks in the basal allochthonous terrane in NW Iberia. The three rock assemblages forming part of the Somozas Mélange may be linked to the evolution of a mature peri-Gondwanan volcanic arc. This volcanic arc was affected by pronounced extension which caused the opening of intra-arc basins, culminating the rifting and subsequent drift of the external parts of the arc during the opening of the Rheic Ocean. This opening started during a time interval constrained by the peak activity in a mature volcanic arc (c. 527-499 Ma) and the generation of intraarc basins around the Cambrian-Ordovician boundary. Tectonic mélanges including high-P rocks have been classically related to subduction zone environments. Regional relationships in NW Iberia and the nature of the rock units involved in the Somozas Mélange, suggest that two different subduction zones generated during oblique convergence and collision between Gondwana and Laurussia were active during the final stages of the assembly of Pangea. The first related to the underthrusting beneath Laurussia of the most external Gondwana margin (c. 370 Ma). The second subduction zone was a new one which accreted later remnants of a peri-Gondwanan arc and sediments of the continental margin below a layer of exhumed high pressure rocks. This oblique collision finished the closure of the Rheic Ocean and contributes to define the new oceanic domain located to the East of Pangea, the Palaeotethys.